Síntese e caracterização de bionanocompósitos magnéticos para liberação controlada de fármacos - Ribeiro, Lígia Nunes de Morais (2013)
The drug delivery systems (DDS) shows several advantages when compared with traditional release systems, such as allowing the employment of lower plasmatic concentrations of drug, having greater efficiency, and minimizing side effects. The improvement of drug delivery depends strictly on the choice of an adequate support allowing to effectively controlling the drug release. All systems use a physical or chemical barrier that control the speedy of release and ensure the desired doses. In this sense, the use of biopolymers and some inorganic hybrid materials as a solid support, such as layered doubles hydroxides (LDH), is of great interest, due to biocompatibility and biodegradability. In this study a series of distinct bionanocomposites were developed and their properties and potential to be used as drug delivery systems explored, creating complexes with high applicability. Gastroresistant and mucoadhesive chitosan-pectin beads for mesalazine release were synthesized in pure form or intercalated LDH compounds, aiming to simulate the in vivo conditions. Another bionanocomposite was also synthesized to be used as a drug carrier consisting of a blend of alginate polysaccharide and magnetic and graphite nanoparticles, in two different pharmaceutical forms: beads and films. This work evaluated the efficacy of these new matrices when the associate drug is previously immobilized on a LDH-based inorganic solid. The compositional and structural characterizations of all these bionanocomposites allowed to conclude that there was an intercalation of the drugs between the LDH layers were satisfactorily, suggesting a compatibility of the system. The physical properties of the beads and films, such as water uptake, encapsulation efficiency, control release, and mechanical properties, were improved when hybridized with the nanoparticles. These results indicate that the bionanocomposites synthesized are promising to further use in drug delivery systems and other substances, exhibiting high applicability in several areas, from biomedicine to agriculture, for example, in the control of fertilizer or herbicides release.